Invasive epiglottic aspergillosis: A case report and literature review. Issue 6 (December 2015) - Ohashi, Toshimitsu; Mizuta, Keisuke; Kuze, Bunya; Aoki, Mitsuhiro; Ito, Yatsuji
Abstract Invasive aspergillosis is a life-threatening infection in immunocompromised hosts and occurs most frequently in the lungs. Invasive laryngeal aspergillosis is extremely rare. Due to the potential progression of invasive aspergillosis, antifungal therapy must be started immediately in cases involving clinical suspicion of the disease. A 65-year-old male with agranulocytosis complained of sore throat and dysphagia. His epiglottis was covered with caseating granulomatous lesions and the tissue was easily disrupted. A histopathological examination showed an aggressive invasion of Aspergillus species and cartilage destruction. Therefore, we made a diagnosis of primary invasive epiglottic aspergillosis. The invasive aspergillosis resolved with antifungal therapy and an increase in neutrophils. It is therefore necessary to include invasive laryngeal aspergillosis in the differential diagnosis when encountering immunocompromised patients presenting with laryngeal granulomatous lesions and laryngitis-like symptoms.